4-H Afterschool Resource Guide: Starting 4-H Clubs in After-School Programs - Sharon K. Junge; Vanessa Spero; Niki Crawson; J. R. Davis; Tara Dorn; Beth Rasa Edwards; Stacy Hall; Karen Henry; Heather Janney; Beth Kerr; Andrea Lazzari; Abby Morgan; et al. (EDIS, 2024)
This resource guide is designed to be used by Extension/4-H professionals and after-school providers to deliver well-formed, positive youth development programs in after-school sites. It includes information on initiating the development of 4-H clubs at after-school sites, volunteer training resources and exercises, how to sustain the clubs, and connections to the community and beyond. The original educational material was edited and revised for this edition by the National Association of 4-H Youth Development Professionals Afterschool Working Group, led by Vanessa Spero. Published by the 4-H Youth Development Department, UF/IFAS Extension, March 2024.